End-member characteristics of sediment grain size in modern Yellow River delta sediments and its environmental significance - Meng, Liwei; Wang, Longsheng; Zhao, Jiawen; Zhan, Chao; Liu, Xianbin; Cui, Buli; Zeng, Lin; Wang, Qing (Frontiers in Marine Science, 2023)
Introduction The sediments of the Yellow River delta record the environmental changes in the Yellow River basin on a long time scale and are sensitive to the river diversion and sedimentary environment evolution. Methods In this study, cores YDC and YDG in the delta near the estuary of the Yellow River since 1976 were taken as the research object, and the parameterized end-member analysis model was used to analyze the grain-size data of the cores. Results The results show that: The main sediments were silty and sand (58% and 77.9%). The grain-size parameters showed opposite changes with wide grain-size ranges and mixed sizes obviously. End member 1 (EM1) and end member 2 (EM2) were composed of clay and fine silt with fine particle sizes of 0.04 mm and 9.8 mm, respectively, and were deposited under weak hydrodynamic conditions during long-distance transport along the Yellow River. End member 3 (EM3) and end member 4 (EM4) were coarse silt with mode particle sizes of 40.14 mm and 66.89 mm, respectively. These were deposited by waves and tidal currents under strong dynamic conditions. Discussion According to the channel changes and the sedimentary facies data of the modern Yellow River delta, before the Yellow River was diverted in 1996, the cores YDC and YDG were both in the estuary-front bar sedimentary environment. In 1996, the Yellow River was diverted to the Qing 8 course. Subsequently, the core YDC changed to the delta-plain sedimentary facies, and the core YDG changed to the delta-front facies. The sediment sources of the two cores changed from the Yellow River sediments to coastal sediment erosion and resuspension. The sedimentary environment changed from siltation to erosion. The results of this study are of great practical significance for estuary management and coastal engineering construction in the modern Yellow River delta and can provide a scientific basis for ecological protection and high-quality development of the Yellow River basin.